Urinary excretion profile of prednisone and prednisolone after different administration routes. Issue 11 (18th December 2019) - Mazzarino, Monica; Piantadosi, Chiara; Comunità, Fabio; de la Torre, Xavier; Botrè, Francesco
Abstract: The urinary excretion profile of prednisolone and prednisone after both systemic (i.e., oral) and topical (i.e., ocular and intranasal) administration was studied by liquid chromatography coupled to mass spectrometry, also to select the most appropriate marker(s) of intake for doping control purposes. Urines were collected from ten subjects every 3 h before and after the administration of therapeutic doses of pharmaceutical formulations containing either prednisone or prednisolone. Samples were subjected to enzymatic hydrolysis (performed for the investigation on the glucuronide profile) followed by liquid/liquid extraction with tert ‐butylmethylether in alkaline conditions. The chromatographic separation was carried out on C18 column, employing as mobile phases ultrapurified water and acetonitrile, both containing 0.1% of formic acid. Detection was achieved using as mass spectrometric analyzer a triple quadrupole, with positive ion electrospray ionization and multiple reaction monitoring as acquisition mode. After both systemic and topical use, the compounds excreted in urine in higher concentration were prednisone, prednisolone and 20β‐dihydro‐prednisolone followed by 20α‐dihydro‐prednisolone and 20α/β‐dihydro‐prednisone. All were excreted mainly as unconjugated compounds, with a maximum of excretion in the first 3–9 h after the administration. After systemic use, prednisone and prednisolone were both detectable for at least 24 h in concentrations ranging from 5 to 500 ng/mL and from 5 to 900 ng/mL respectively. Whereas, after topical administration, prednisone and prednisolone were detectable for at least 18 h in concentrations ranging from 5 to 140 ng/mL and from 5 to 50 ng/mL respectively. Abstract : The urinary excretion profile of prednisolone and prednisone after both systemic and topical administration was defined by LC–MS/MS to select the most appropriate marker(s) of use. After both systemic and topical use, the compounds excreted in urine in higher concentration were prednisone, prednisolone and 20β‐dihydro‐prednisolone. They were excreted mainly as unconjugated compounds, with a maximum in the first 3–9 h from administration. Prednisone, prednisolone and 20β‐dihydro‐prednisolone reached level higher than the reporting level (30 ng/mL) after all the routes studied.